Preparation method of high-activity palladium catalyst

By selecting a high specific surface area support and cocatalyst, combining specific palladium sources and preparation steps, the problem of low loading efficiency of palladium catalysts is solved, and a high activity and stability of palladium catalyst preparation is achieved, which is suitable for a variety of catalytic reactions.

CN119500180APending Publication Date: 2025-02-25HUIZHOU JINSHENG NEW ELECTRONIC TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411542133.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

When preparing palladium catalysts with existing silicon oxide support, the palladium loading efficiency is low, which affects the catalytic performance.

Method used

Highly active palladium catalysts are prepared by impregnation and reduction steps using specific palladium sources, support with high specific surface area (such as activated carbon, alumina, carbon nanotubes) and suitable cocatalysts (such as metal oxides).

Benefits of technology

It improves the catalytic activity and stability of palladium catalysts, is suitable for more demanding reaction conditions, extends the service life of the catalyst, and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005113026420000081
    Figure BDA0005113026420000081
  • Figure BDA0005113026420000091
    Figure BDA0005113026420000091
Patent Text Reader

Abstract

The invention relates to the technical field of catalyst preparation, and particularly discloses a preparation method of a high-activity palladium catalyst. The preparation method of the high-activity palladium catalyst comprises the following steps: (1) dissolving palladium chloride or palladium nitrate in deionized water to form a palladium solution; (2) adding a carrier into the palladium solution, and dipping at 40-60 DEG C for 12-24 hours to obtain a mixture; and (3) adding a cocatalyst into the mixture, and reducing for 2-4 hours at 250-300 DEG C in a hydrogen atmosphere to obtain the high-activity palladium catalyst, the carrier is one of activated carbon, aluminum oxide and carbon nanotubes; the cocatalyst is a metal oxide. The high-activity palladium catalyst prepared in the invention has high catalytic activity, and through cooperation with process parameters of the preparation steps, sufficient adsorption and reduction of palladium ions are ensured, so that the catalytic effect is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of catalyst preparation, and more specifically, to a method for preparing a high-activity palladium catalyst. Background Art

[0002] As an important precious metal catalyst, palladium is widely used in the fields of chemical industry, energy, environmental protection, etc. There are various methods for preparing palladium catalysts, usually using the impregnation-precipitation method, which combines the advantages of the impregnation method and the precipitation method. The solution containing palladium salt is impregnated into the carrier, and then the palladium is fixed on the carrier through precipitation reaction, and then the catalyst is obtained through drying, roasting and other processes.

[0003] In the prior art, silicon oxide is used as a carrier material to prepare palladium catalysts. Silicon oxide has good thermal stability and high thermal resistance, can maintain structural stability at high temperatures, and is suitable for catalytic reactions that require high temperature treatment. However, the loading efficiency of palladium on silicon oxide is affected by the pore structure of the silicon oxide carrier, resulting in the ineffective use of part of the palladium, which in turn affects the catalytic performance of palladium. Summary of the invention

[0004] In order to improve the problem of poor catalytic performance of palladium catalysts prepared using silicon oxide carriers, the present application provides a method for preparing a high-activity palladium catalyst.

[0005] In a first aspect, the present application provides a method for preparing a highly active palladium catalyst, using the following technical solution: A method for preparing a highly active palladium catalyst, comprising the following steps: (1) dissolving palladium chloride or palladium nitrate in deionized water to form a palladium solution; (2) adding the carrier to the palladium solution of step (1), and immersing at 40-60° C. for 12-24 hours to obtain a mixture; (3) adding a promoter to the mixture in step (2), and reducing the mixture at 250-300° C. for 2-4 h in a hydrogen atmosphere to obtain a highly active palladium catalyst; The carrier is one of activated carbon, alumina and carbon nanotubes; The promoter is a metal oxide.

[0006] By adopting the above technical scheme, by selecting a specific palladium source, a carrier with a high specific surface area and a suitable co-catalyst, the prepared palladium catalyst has a higher catalytic activity, and the process parameters of the preparation steps, such as the temperature and time of impregnation and reduction, are coordinated to ensure that the palladium ions are fully adsorbed and reduced, thereby enhancing the catalytic effect.

[0007] A carrier with a high specific surface area is selected to improve the dispersion and catalytic activity of palladium. The catalyst is immersed at 40-60°C for 12-24 hours to ensure that the palladium ions can be fully adsorbed on the carrier. A co-catalyst is introduced to enhance the stability and catalytic performance of the catalyst. The combination of the co-catalyst and the carrier improves the stability of the palladium activator. This stability is not only reflected in the catalytic reaction process, but also in the fact that it can maintain good catalytic performance after long-term storage and use. The catalyst is reduced at 250-300°C for 2-4 hours to ensure that the palladium ions are fully reduced to metallic palladium.

[0008] Activated carbon has a developed pore structure and a huge specific surface area, which can provide a large number of active sites, which is conducive to adsorption and catalytic reactions. Activated carbon has good stability and is not easy to react chemically with reactants or products, which ensures the long-term use of the carrier. Alumina has good thermal stability and can maintain structural stability at high temperatures. It is not easy to react chemically with reactants or products, which ensures the stability of the catalyst; and the pore structure of alumina can be regulated, which is conducive to improving the utilization rate of the inner surface of the catalyst and improving the catalytic activity and selectivity. Carbon nanotubes have a large specific surface area and can provide more active sites, which is conducive to adsorption and catalytic reactions; and the structure of carbon nanotubes is stable and not easily destroyed by chemical substances, which ensures the long-term use of the carrier.

[0009] As a co-catalyst, metal oxide has good thermal stability and chemical stability, can maintain the stability of structure and performance in high temperature and extreme chemical environment, and synergizes with the main catalyst as an active site to promote the adsorption and activation of reactants, thereby improving catalytic activity and selectivity. The high-activity palladium catalyst prepared by the above steps in this application has higher catalytic activity and stability, and is suitable for more demanding reaction conditions.

[0010] Optionally, the pore size of the high-activity palladium catalyst is 100-500ppi, and the palladium particles on the surface are nanoparticles with a particle size of 200-400nm.

[0011] By adopting the above technical solution, the pore size of the high-activity palladium catalyst can provide more diffusion channels, reduce diffusion resistance, facilitate the rapid adsorption of reactants and timely desorption of products, thereby increasing the rate of catalytic reaction, and can also provide more surface and internal active sites, increase the contact area between reactants and catalysts, and improve catalytic efficiency. At the same time, high porosity helps to avoid active sites from being blocked and maintain the long-term activity of the catalyst.

[0012] The appropriate particle size of nanoparticles can provide more active sites, which is beneficial to improving catalytic activity and selectivity, reducing the diffusion distance of reactants and products inside the catalyst, reducing diffusion resistance, and increasing reaction rate. At the same time, the appropriate particle size helps to increase the penetration depth of reactants and make full use of the internal active sites of the catalyst.

[0013] Optionally, the promoter is copper oxide or cobalt oxide.

[0014] By adopting the above technical solution, copper oxide or cobalt oxide can form a metal-oxide interface with palladium, change the electronic structure of palladium, and improve its catalytic activity. Copper oxide or cobalt oxide also acts as an electron donor or acceptor, which can promote the transfer of electrons between reactants and palladium catalysts, accelerate the catalytic cycle, and increase the reaction rate.

[0015] Optionally, in step (2), the mixture is immersed in a chloroplatinic acid solution to obtain a complex, a co-catalyst is added to the complex, and the complex is reduced in a hydrogen atmosphere to obtain a high-activity palladium-platinum bimetallic catalyst.

[0016] By adopting the above technical solution, platinum metal elements are introduced to form a multi-metal catalyst with palladium, which changes the electron transfer and surface structure between metals to improve the synergistic effect of the catalyst and improve the overall activity, catalytic efficiency and selectivity of the catalyst. Multi-metal catalysts have better thermal and chemical stability than palladium catalysts. The addition of platinum metal can prevent the sintering and agglomeration of palladium under high temperature or extreme reaction conditions, and extend the service life of the catalyst. In addition, the corrosion resistance of platinum also helps to improve the stability of the catalyst in harsh environments.

[0017] Optionally, in step (2), the catalyst is immersed in a rhodium nitrate solution to obtain a complex, a co-catalyst is added to the complex, and the complex is reduced in a hydrogen atmosphere to obtain a high-activity palladium-rhodium bimetallic catalyst.

[0018] By adopting the above technical solution, rhodium metal elements are introduced to form a multi-metal catalyst with palladium, which can produce a synergistic catalytic effect and improve the overall activity, selectivity and catalytic efficiency of the catalyst. Metal catalysts have better thermal and chemical stability. The addition of rhodium metal can prevent the sintering and agglomeration of palladium under high temperature or extreme reaction conditions, thereby extending the service life of the catalyst. In addition, the corrosion resistance of rhodium also helps to improve the stability of the catalyst in harsh environments.

[0019] Optionally, the carrier is pretreated, comprising the following steps: dispersing the carrier in deionized water, ultrasonicating at a temperature of 80-85°C for 1-2h, then adding carboxymethyl cellulose and modified graphene, stirring at a temperature of 90-95°C for 1-2h, filtering, and drying to obtain a pretreated carrier.

[0020] By adopting the above technical scheme, the carrier is ultrasonicated at a certain temperature to make the carrier evenly dispersed, and carboxymethyl cellulose is added to disperse the carboxymethyl cellulose in deionized water, so that the solution becomes viscous to obtain a gel solution. The carboxymethyl cellulose can not only prevent the palladium metal from agglomerating under the reaction conditions and maintain the nanometer size of the palladium metal, thereby improving the activity and selectivity of the catalyst, but also increase the adsorption of the carrier, so that the palladium metal is fixed on the carrier.

[0021] Modified graphene can be loaded on a carrier, carboxymethyl cellulose makes the modified graphene and the carrier bond more tightly, and the modified graphene has an extremely high specific surface area and a unique two-dimensional structure, which can provide more active sites, enhance the stability of the palladium catalyst, and make the palladium metal more evenly dispersed on the graphene surface, thereby improving the catalytic activity of the catalyst. The pretreated carrier obtained by combining the three has a large specific surface area, and the palladium catalyst prepared subsequently has high catalytic properties and stability.

[0022] Optionally, the mass ratio of the carrier, carboxymethyl cellulose and modified graphene is 1g:0.2-0.4g:30-40mg.

[0023] By adopting the above technical scheme, the mass ratio of the carrier, carboxymethyl cellulose and modified graphene is further limited within a certain range, the obtained carrier has a larger specific surface area, the modified graphene can be loaded on the carrier, the carboxymethyl cellulose makes the modified graphene and the carrier bond more tightly, increases the specific surface area of ​​the carrier, and enables the carrier to provide more active sites, promotes the mass transfer of reactants and products, reduces the mass transfer resistance, and improves the catalytic efficiency; graphene provides a high specific surface area and good conductivity, while carboxymethyl cellulose provides stability and good dispersibility, and the combination of the two can significantly improve the performance of the carrier.

[0024] Optionally, the preparation method of the modified graphene comprises the following steps: adding graphene to deionized water, ultrasonically stirring for 25-30 minutes to obtain a graphene suspension; adding sodium dodecyl sulfate to the graphene suspension, ultrasonicating, and then adding nano-silicon dioxide and polyvinyl pyrrolidone, stirring evenly, filtering, and drying to obtain modified graphene.

[0025] By adopting the above technical solution, sodium dodecyl sulfate can be adsorbed on the surface of graphene, and through electrostatic repulsion and hydrophobic effect, it can effectively prevent the re-aggregation of graphene sheets and improve the dispersibility of graphene in deionized water. Nano-silicon dioxide can be loaded on the surface of graphene, increasing the specific surface area of ​​graphene, and subsequently applied to the carrier to provide more active sites, increase the contact area between palladium metal and reactants, improve catalytic efficiency, and effectively disperse palladium metal particles to prevent them from agglomerating during the reaction process, thereby improving the stability of the catalyst and extending its service life.

[0026] Polyvinyl pyrrolidone has good dispersibility and viscosity, which can make nano-silicon dioxide stably adhere to the surface of graphene, increasing the stability and dispersibility of the modified graphene. Polyvinyl pyrrolidone can also prevent palladium metal particles from agglomerating during the preparation and use process, thereby improving the dispersibility of palladium metal on the carrier. The combination of the three increases the specific surface area and dispersibility of the modified graphene, and the subsequent application on the carrier improves the comprehensive performance of the carrier.

[0027] Optionally, the mass ratio of the graphene, nano-silicon dioxide and polyvinyl pyrrolidone is 1 mg: 0.3-0.5 g: 0.06-0.08 g.

[0028] By adopting the above technical scheme, the mass ratio of graphene, nano-silicon dioxide and polyvinyl pyrrolidone is further limited within a certain range, the specific surface area of ​​graphene is increased, the nano-silicon dioxide can be loaded on the surface of graphene, the specific surface area of ​​graphene is increased, and polyvinyl pyrrolidone enables the nano-silicon dioxide to stably adhere to the surface of graphene, thereby increasing the stability and dispersibility of the modified graphene. The combination of graphene, nano-silicon dioxide and polyvinyl pyrrolidone has a synergistic effect, thereby increasing the specific surface area and catalytic performance of the carrier.

[0029] In a second aspect, a high-activity palladium catalyst is prepared by the above method.

[0030] In summary, this application has the following beneficial effects: 1. In the present application, a specific palladium source, a carrier with a high specific surface area and a suitable co-catalyst are selected to improve the catalytic activity of the palladium activator, and a suitable impregnation and reduction temperature and time are set to ensure that the palladium ions are fully adsorbed and reduced, thereby enhancing the catalytic effect; the introduction of the co-catalyst and the carrier modification treatment significantly improves the stability of the palladium activator, and this stability is not only reflected in the catalytic reaction process, but also in the fact that it can still maintain good catalytic performance after long-term storage and use.

[0031] 2. Due to the improvement of catalytic activity and stability in the present application, the palladium activator prepared in the present application requires less usage under the same reaction conditions compared with traditional catalysts, thereby reducing costs. At the same time, its longer service life reduces the need for frequent replacement of catalysts, further saving costs.

[0032] 3. The preparation method of the present application has high flexibility. The composition and process parameters of the composition can be adjusted according to specific needs to meet the requirements of different catalytic reactions, so that the present invention has a wide range of application potentials in various organic synthesis reactions; the present application reduces the generation and emission of harmful substances and reduces the impact on the environment. In addition, improving the activity and stability of the catalyst also helps to reduce the consumption and waste of the catalyst, which is in line with the principles of green chemistry. DETAILED DESCRIPTION

[0033] Preparation Example of Pretreated Support Preparation Example 1-1 The carrier is pretreated, including the following steps: 5 g of the carrier is dispersed in 10 mL of deionized water, ultrasonicated at a temperature of 85° C. for 2 h, then carboxymethyl cellulose and modified graphene are added, stirred at a temperature of 95° C. for 2 h, filtered, and dried to obtain a pretreated carrier.

[0034] The mass ratio of the carrier, carboxymethyl cellulose and modified graphene is 1g:0.2g:30mg.

[0035] The preparation method of modified graphene comprises the following steps: adding 0.1 g of graphene into 10 mL of deionized water, and ultrasonically stirring for 30 minutes to obtain a graphene suspension; adding 0.05 g of sodium dodecyl sulfate into the graphene suspension, ultrasonically stirring for 2 hours, and then adding nano-silicon dioxide and polyvinyl pyrrolidone, stirring evenly, filtering, and drying to obtain the modified graphene.

[0036] The mass ratio of graphene, nano-silicon dioxide and polyvinyl pyrrolidone is 1 mg:0.5 g:0.06 g.

[0037] Preparation Example 1-2 The difference from Preparation Example 1-1 is that carboxymethyl cellulose is not added.

[0038] Preparation Example 1-3 The difference from Preparation Example 1-1 is that no modified graphene is added.

[0039] Preparation Example 1-4 The difference from Preparation Example 1-1 is that the mass ratio of the carrier, carboxymethyl cellulose and modified graphene is 1 g:0.4 g:40 mg.

[0040] Preparation Example 1-5 The difference from Preparation Example 1-1 is that the mass ratio of the carrier, carboxymethyl cellulose and modified graphene is 1 g:0.8 g:25 mg.

[0041] Preparation Example 1-6 The difference from Preparation Example 1-1 is that no nano-silicon dioxide is added in the preparation method of modified graphene.

[0042] Preparation Example 1-7 The difference from Preparation Example 1-1 is that polyvinyl pyrrolidone is not added in the preparation method of modified graphene.

[0043] Preparation Example 1-8 The difference from Preparation Example 1-1 is that the mass ratio of graphene, nano-silicon dioxide and polyvinyl pyrrolidone is 1 mg:0.3 g:0.08 g.

[0044] Preparation Example 1-9 The difference from Preparation Example 1-1 is that the mass ratio of graphene, nano-silicon dioxide and polyvinyl pyrrolidone is 1 mg:0.1 g:0.12 g. Example

[0045] Example 1 A method for preparing a high-activity palladium catalyst comprises the following steps: (1) dissolving palladium chloride in 1 L of deionized water to form a 0.1 mol / L palladium solution; (2) adding 80 g of activated carbon to the palladium solution of step (1), and immersing at 40° C. for 12 h to obtain a mixture; (3) Add 30 g of copper oxide to the mixture in step (2), and reduce it at 250° C. for 2 h in a hydrogen atmosphere to obtain a highly active palladium catalyst.

[0046] Example 2 A method for preparing a high-activity palladium catalyst, which is different from Example 1 in that the impregnation temperature is 50° C., the impregnation time is 24 h, the reduction temperature is 280° C., and the reduction time is 4 h.

[0047] Example 3 A method for preparing a high-activity palladium catalyst, which is different from Example 1 in that the impregnation temperature is 60° C., the impregnation time is 16 h, the reduction temperature is 300° C., and the reduction time is 3 h.

[0048] Example 4 A method for preparing a high-activity palladium catalyst, which differs from Example 1 in that the activated carbon is replaced by aluminum oxide.

[0049] Example 5 A method for preparing a high-activity palladium catalyst, which differs from Example 1 in that activated carbon is replaced by carbon nanotubes.

[0050] Example 6 A method for preparing a high-activity palladium catalyst, which differs from Example 1 in that copper oxide is replaced by cobalt oxide.

[0051] Example 7 A method for preparing a high-activity palladium catalyst, which differs from Example 1 in that it comprises the following steps: (1) dissolving palladium chloride in 1 L of deionized water to form a 0.1 mol / L palladium solution; (2) adding 80 g of activated carbon to the palladium solution of step (1), immersing at 45° C. for 20 h to obtain a mixture, and then immersing the mixture in 1 L of 0.1 mol / L chloroplatinic acid solution, immersing at 45° C. for 8 h to obtain a composite; (3) Add 30 g of copper oxide to the composite in step (2), and reduce it at 260° C. for 4 h in a hydrogen atmosphere to obtain a highly active palladium-platinum bimetallic catalyst.

[0052] Example 8 A method for preparing a high-activity palladium catalyst, which differs from Example 7 in that the chloroplatinic acid solution is replaced with a rhodium nitrate solution to obtain a high-activity palladium-rhodium bimetallic catalyst.

[0053] Example 9 A method for preparing a high-activity palladium catalyst, which differs from Example 1 in that an activated carbon carrier is pretreated, and the carrier pretreatment is prepared using Preparation Example 1-1.

[0054] Example 10 A method for preparing a high-activity palladium catalyst, which differs from Example 9 in that an activated carbon carrier is pretreated, and the carrier pretreatment is prepared using Preparation Example 1-2.

[0055] Embodiment 11 A method for preparing a high-activity palladium catalyst, which differs from Example 9 in that the activated carbon carrier is pretreated, and the carrier pretreatment is prepared using Preparation Example 1-3.

[0056] Example 12 A method for preparing a high-activity palladium catalyst, which differs from Example 9 in that the activated carbon carrier is pretreated, and the carrier pretreatment is prepared using Preparation Example 1-4.

[0057] Example 13 A method for preparing a high-activity palladium catalyst, which differs from Example 9 in that the activated carbon carrier is pretreated, and the carrier pretreatment is prepared using Preparation Example 1-5.

[0058] Embodiment 14 A method for preparing a high-activity palladium catalyst, which differs from Example 9 in that the activated carbon carrier is pretreated, and the carrier pretreatment is prepared using Preparation Example 1-6.

[0059] Embodiment 15 A method for preparing a high-activity palladium catalyst, which differs from Example 9 in that the activated carbon carrier is pretreated, and the carrier pretreatment is prepared using Preparation Example 1-7.

[0060] Example 16 A method for preparing a high-activity palladium catalyst, which differs from Example 9 in that the activated carbon carrier is pretreated, and the carrier pretreatment is prepared using Preparation Example 1-8.

[0061] Embodiment 17 A method for preparing a high-activity palladium catalyst, which differs from Example 9 in that the activated carbon carrier is pretreated, and the carrier pretreatment is prepared using Preparation Example 1-9.

[0062] Comparative Example Comparative Example 1 A method for preparing a high-activity palladium catalyst, which is different from Example 1 in that the carrier is silicon oxide.

[0063] Comparative Example 2 A method for preparing a high-activity palladium catalyst, which differs from Example 1 in that no promoter is added.

[0064] Performance testing The high-activity palladium catalysts prepared in Examples 1-17 and Comparative Examples 1-2 were subjected to performance tests; The palladium loading was measured by ICP-MS, the dispersion was measured by SEM, EDS and HOT analysis, and the catalytic activity of the anthraquinone hydrogenation reaction to generate hydrogen peroxide and the purity of the product of the anthraquinone hydrogenation reaction to generate hydrogen peroxide were tested by high performance liquid chromatography. The test results are shown in Table 1.

[0065] Table 1 Test data of embodiments and comparative examples Combining the data in the embodiments and Table 1, it can be seen that the high-activity palladium catalysts prepared in Examples 1-6 have good catalytic activity, wherein the palladium loading of Example 2 is 0.43%, the dispersity is 43.9%, the catalytic activity of the reaction of anthraquinone hydrogenation to generate hydrogen peroxide is 8.290g / L, the product purity of the reaction of anthraquinone hydrogenation to generate hydrogen peroxide is 95%, the pore size of the high-activity palladium catalyst is 400ppi, and the palladium particles on the surface are nanoparticles with a particle size of 300nm. The pore size of the high-activity palladium catalyst of Example 1 is 100ppi, and the palladium particles on the surface are nanoparticles with a particle size of 200nm. The pore size of the high-activity palladium catalyst of Example 3 is 500ppi, and the palladium particles on the surface are nanoparticles with a particle size of 400nm.

[0066] It shows that the palladium catalyst prepared in this application has high catalytic activity by selecting a specific palladium source, a carrier with a high specific surface area and a suitable co-catalyst, and the process parameters of the preparation steps, such as the temperature and time of impregnation and reduction, are coordinated to ensure that the palladium ions are fully adsorbed and reduced, thereby enhancing the catalytic effect.

[0067] In Examples 4-5, the activated carbon is replaced by aluminum oxide or carbon nanotubes, and in Example 6, the copper oxide is replaced by cobalt oxide. The palladium loading, dispersion, catalytic activity of the reaction of anthraquinone hydrogenation to generate hydrogen peroxide, and product purity of the reaction of anthraquinone hydrogenation to generate hydrogen peroxide all have good performance, indicating that the high-activity palladium catalyst prepared by the above steps in the present application has higher catalytic activity and stability, and is suitable for more stringent reaction conditions.

[0068] In Example 7, in step (2), the mixture is immersed in a chloroplatinic acid solution to obtain a high-activity palladium-platinum bimetallic catalyst. As shown in Table 1, the palladium loading is 0.49%, the dispersion is 45.2%, the catalytic activity of the reaction of anthraquinone hydrogenation to generate hydrogen peroxide is 8.456 g / L, and the product purity of the reaction of anthraquinone hydrogenation to generate hydrogen peroxide is 98%. This indicates that the introduction of platinum metal elements to form a multi-metal catalyst with palladium changes the electron transfer and surface structure between metals to improve the synergistic effect of the catalyst, and improve the overall activity, catalytic efficiency and selectivity of the catalyst.

[0069] In Example 8, in step (2), the mixture is immersed in a rhodium nitrate solution to obtain a high-activity palladium-rhodium bimetallic catalyst. As shown in Table 1, the palladium loading is 0.48%, the dispersion is 45.1%, the catalytic activity of the reaction of anthraquinone hydrogenation to generate hydrogen peroxide is 8.455 g / L, and the product purity of the reaction of anthraquinone hydrogenation to generate hydrogen peroxide is 98%. This shows that the introduction of rhodium metal elements to form a multi-metal catalyst with palladium can produce a synergistic catalytic effect and improve the overall activity, selectivity and catalytic efficiency of the catalyst.

[0070] In Example 9, Example 12 and Example 16, the activated carbon carrier was pretreated. As shown in Table 1, the palladium loading was 0.64%, the dispersion was 51.2%, the catalytic activity of the reaction of anthraquinone hydrogenation to generate hydrogen peroxide was 9.879 g / L, and the product purity of the reaction of anthraquinone hydrogenation to generate hydrogen peroxide was >99%. The pretreated activated carbon has a large specific surface area, the modified graphene can be loaded on the carrier, the carboxymethyl cellulose makes the modified graphene and the carrier bond more closely, and the palladium metal is more evenly dispersed on the graphene surface, thereby improving the catalytic activity of the catalyst.

[0071] In Example 10, carboxymethyl cellulose is not added during the pretreatment of the carrier, and modified graphene is not added in Example 11. In Example 13, the mass ratio of the carrier, carboxymethyl cellulose and modified graphene is changed. As can be seen from Table 1, compared with Example 9, the palladium loading, dispersity, catalytic activity of the reaction of anthraquinone hydrogenation to generate hydrogen peroxide, and product purity of the reaction of anthraquinone hydrogenation to generate hydrogen peroxide in Examples 10-11 are all reduced, but the palladium loading, dispersity, catalytic activity of the reaction of anthraquinone hydrogenation to generate hydrogen peroxide, and product purity of the reaction of anthraquinone hydrogenation to generate hydrogen peroxide in Example 13 are all greater than those in Examples 10-11, but less than those in Example 9, indicating that modified graphene can be loaded on the carrier, and carboxymethyl cellulose makes the modified graphene and the carrier bond more closely, increases the specific surface area of ​​the carrier, and provides more active sites for the carrier, promotes mass transfer of reactants and products, reduces mass transfer resistance, and improves catalytic efficiency.

[0072] In the preparation method of modified graphene in Example 14, nano-silicon dioxide is not added, and polyvinyl pyrrolidone is not added in Example 15. In Example 17, the mass ratio of graphene, nano-silicon dioxide and polyvinyl pyrrolidone is changed. As can be seen from Table 1, compared with Example 9, the palladium loading, dispersity, catalytic activity of anthraquinone hydrogenation to generate hydrogen peroxide reaction, and product purity of anthraquinone hydrogenation to generate hydrogen peroxide reaction values ​​of Examples 14-15 are all decreased, but the palladium loading, dispersity, catalytic activity of anthraquinone hydrogenation to generate hydrogen peroxide reaction, and product purity of anthraquinone hydrogenation to generate hydrogen peroxide reaction values ​​of Example 17 are all greater than those of Examples 14-15, but less than those of Example 9, indicating that nano-silicon dioxide can be loaded on the surface of graphene, increasing the specific surface area of ​​graphene, and polyvinyl pyrrolidone allows nano-silicon dioxide to stably adhere to the surface of graphene, increasing the stability and dispersibility of modified graphene, and the coordination of graphene, nano-silicon dioxide and polyvinyl pyrrolidone has a synergistic effect, thereby improving the specific surface area and catalytic performance of the carrier.

[0073] Comparative Example 1 The carrier is silicon oxide. As shown in Table 1, the palladium loading is 0.37%, the dispersion is 40.2%, the catalytic activity of the reaction of anthraquinone hydrogenation to generate hydrogen peroxide is 8.271 g / L, and the product purity of the reaction of anthraquinone hydrogenation to generate hydrogen peroxide is 90%. This shows that the carrier of the present application has a developed pore structure and a huge specific surface area, can provide a large number of active sites, is conducive to the adsorption and catalytic reaction, and improves the catalytic activity.

[0074] Comparative Example 2 does not add a promoter. As shown in Table 1, the palladium loading is 0.34%, the dispersion is 39.7%, the catalytic activity of the reaction of anthraquinone hydrogenation to generate hydrogen peroxide is 8.254 g / L, and the product purity of the reaction of anthraquinone hydrogenation to generate hydrogen peroxide is 87%. This shows that the promoter works synergistically with the main catalyst, serving as an active site to promote the adsorption and activation of the reactants, thereby improving the catalytic activity and stability.

[0075] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing a highly active palladium catalyst, characterized in that: The steps include: (1) dissolving palladium chloride or palladium nitrate in deionized water to form a palladium solution; (2) adding the carrier to the palladium solution of step (1), and immersing at 40-60° C. for 12-24 hours to obtain a mixture; (3) adding a promoter to the mixture in step (2), and reducing the mixture at 250-300° C. for 2-4 h in a hydrogen atmosphere to obtain a highly active palladium catalyst; The carrier is one of activated carbon, alumina and carbon nanotubes; The promoter is a metal oxide.

2. A method for preparing a highly active palladium catalyst according to claim 1, characterized in that, The pore size of the high-activity palladium catalyst is 100-500ppi, and the palladium particles on the surface are nanoparticles with a particle size of 200-400nm.

3. A method for preparing a highly active palladium catalyst according to claim 1, characterized in that: The promoter is copper oxide or cobalt oxide.

4. A method for preparing a highly active palladium catalyst according to claim 1, characterized in that: In step (2), the mixture is immersed in a chloroplatinic acid solution to obtain a composite, a co-catalyst is added to the composite, and the composite is reduced in a hydrogen atmosphere to obtain a high-activity palladium-platinum bimetallic catalyst.

5. A method for preparing a highly active palladium catalyst according to claim 1, characterized in that: In step (2), the catalyst is immersed in a rhodium nitrate solution to obtain a complex, a co-catalyst is added to the complex, and the complex is reduced in a hydrogen atmosphere to obtain a high-activity palladium-rhodium bimetallic catalyst.

6. A method for preparing a highly active palladium catalyst according to claim 1, characterized in that: The carrier is pretreated, comprising the following steps: dispersing the carrier in deionized water, ultrasonicating at a temperature of 80-85°C for 1-2h, then adding carboxymethyl cellulose and modified graphene, stirring at a temperature of 90-95°C for 1-2h, filtering, and drying to obtain a pretreated carrier.

7. A method for preparing a highly active palladium catalyst according to claim 6, characterized in that: The mass ratio of the carrier, carboxymethyl cellulose and modified graphene is 1g:0.2-0.4g:30-40mg.

8. A method for preparing a highly active palladium catalyst according to claim 6, characterized in that: The preparation method of modified graphene comprises the following steps: adding graphene to deionized water, and ultrasonically stirring for 25-30 minutes to obtain a graphene suspension; adding sodium dodecyl sulfate to the graphene suspension, ultrasonicating, and then adding nano silicon dioxide and polyvinyl pyrrolidone, stirring evenly, filtering, and drying to obtain the modified graphene.

9. A method for preparing a highly active palladium catalyst according to claim 8, characterized in that: The mass ratio of the graphene, nano-silicon dioxide and polyvinyl pyrrolidone is 1 mg: 0.3-0.5 g: 0.06-0.08 g.

10. A high-activity palladium catalyst prepared by the method according to any one of claims 1 to 9.